Phylotypic Characterization of Mycobionts and Photobionts of Rock Tripe Lichen in East Antarctica - Merry Sailonga Faluaburu; Ryosuke Nakai; Satoshi Imura; Takeshi Naganuma (Microorganisms, 2019)
Saxicolous rock ripe lichens that grow on rocks in the East Antarctic fellfields were sampled for phylotypic characterization of its constituent mycobionts (fungi) and photobionts (algae and cyanobacteria). The rock tripe lichen-forming fungal and algal phylotypes were classified under the common lichen-forming genera of ascomycetes, namely, Umbilicaria , and green algae, namely, Trebouxia and Coccomyxa . However, phylotypes of the green algal chloroplasts and the lichen-associated cyanobacteria showed unexpectedly high diversity. The detected chloroplast phylotypes were not fully affiliated with the green algal genera Trebouxia or Coccomyxa . The predominant chloroplast phylotype demonstrated maximum resemblance to Neglectella solitaria , which is neither a known Antarctic species nor a typical lichen photobiont. Another dominant chloroplast phylotype belonged to the atypical Antarctic green algae family. Cyanobacterial phylotypes were dominated by those affiliated with the Microcoleus species rather than the well-known lichen-associates, Nostoc species. The occurrences of these Microcoleus -affiliated cyanobacterial phylotypes were specifically abundant within the Yukidori Valley site, one of the Antarctic Specially Protected Areas (ASPA). The ASPA site, along with another 50 km-distant site, yielded most of the cryptic diversity in the phylotypes of chloroplasts and cyanobacteria, which may contribute to the phenotypic variability within the rock tripe lichen photobionts.